2016
DOI: 10.7747/jfes.2016.32.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity, Tree Regeneration, Biomass Production and Carbon Storage in Different Oak Forests on Ridge Tops of Garhwal Himalaya

Abstract: The present study was conducted on ridge tops of moist temperate Oak forests in Garhwal Himalaya to assess the plant diversity, regeneration, biomass production and carbon assimilation in different Oak forests. For this purpose, ). The total biomass density (TBD) across three Oak forests ranged between 497.32±83.70 (FT1) and 663.16±93.85 t ha -1 (FT3), while the total carbon density (TCD) values ranged between 228.75±22.27 (FT1) and 304.31±18.12 t ha -1 (FT3). Most of the tree species were found with good rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the Western Himalayan region, the effects of both elevation and climate change on forest composition are evident, but they need to be measured in more detail (Sharma, Mishra, et al 2016a, 2016bSharma, Tiwari, et al 2016). An assessment of species regeneration along the elevational gradient is critical in order to explore compositional changes and species migration in Himalayan forests.…”
Section: Systems Knowledgementioning
confidence: 99%
“…In the Western Himalayan region, the effects of both elevation and climate change on forest composition are evident, but they need to be measured in more detail (Sharma, Mishra, et al 2016a, 2016bSharma, Tiwari, et al 2016). An assessment of species regeneration along the elevational gradient is critical in order to explore compositional changes and species migration in Himalayan forests.…”
Section: Systems Knowledgementioning
confidence: 99%
“…More recently, particular attention has been given to documenting the relative abundance and likely regeneration of Q. semecarpifolia in relation to other tree species in locations such as ridge forests of Western Himalaya (Malik and Bhatt, 2016;Sharma et al, 2016;Tiwari et al, 2018, Tewari et al, 2019. Nearly 70% of such studies have reported very poor regeneration in natural stands.…”
Section: Introductionmentioning
confidence: 99%
“…It is a characteristic tree of Western Himalayan upper oak/fir forest types, generally predominating on the exposed ridges. In the Western Himalayas, it is well distributed across various elevational ranges, that is, 2,000-3,500 m asl in the Western Himalayas (Vetaas, 1997Vetaas and Chaudhary, 1998;Rawat et al, 2021a,b); 2,400-3,540 m asl in the Garhwal Himalayas (Singh et al, 1997;Sharma et al, 2016); 2,400-3,500 m asl in the Kumaun Himalayas (Saran et al, 2010) and ascending to approximately 4,000 m elevation on northern and southern aspects, respectively. According to Orwa et al (2009), the suitable native range for plantation of this species is Afghanistan, China, India, and Pakistan and the exotic range includes France (Figure 1).…”
Section: Distributionmentioning
confidence: 99%